Immunosenescence-related T cell phenotypes, structural brain imaging, and cognitive impairment in patients with schizophrenia: a moderated mediation analysis - Na Li; Yanli Li; Ting Yu; Wenjin Chen; Mengzhuang Gou; Wenkai Zheng; Zhaofan Liu; Xiaoying Wang; Jiao Fang; Jinghui Tong; Song Chen; Baopeng Tian; et al. (Schizophrenia)
Abstract Cognitive impairment is a core characteristic of schizophrenia. Immunosenescence has been consistently implicated in the cognitive dysfunction observed in neurodegenerative diseases, but how it may relate to cognitive deficits in schizophrenia is still unclear. We explored the associations between immunosenescence and cognitive impairment in patients with schizophrenia (SCZ, n = 65) and healthy controls (HCs, n = 39). Immunosenescence markers were assessed by flow cytometry and included the percentage of naïve or memory T cell subsets labeled by CD4+/CD8+, CD45RA+(naïve)/CD45RO (memory), or CD95+(memory), as well as the intracellular levels of selected cytokines (IL-1β, IL-6, TNF-α, and IFN-γ) in T cell subsets. T1-weighted magnetic resonance imaging was performed to assess the subcortical volume and cortical thickness. Participants were evaluated using the Positive and Negative Syndrome Scale and the Chinese version of the MATRICS Consensus Cognitive Battery.The results indicated that (1) Compared with HCs, SCZ patients were characterized by fewer naïve and more memory T cell subsets, accompanied by altered intracellular cytokine levels, indicating immunosenescence phenotypes. (2) The intracellular IL-1β level in naïve CD8+CD45RA+CD95+ T cells was associated with working memory deficit in SCZ patients. (3) In a moderated mediation model, the effect of the IL-1β level on the working memory score was mediated by the thickness of the right inferior parietal lobule (IPL_R), and the volume of the right choroid plexus (CP) moderated the indirect pathway between the IL-1β level and IPL_R thickness. Our findings highlighted immunosenescence-related T cell phenotypes and the CP as potential biomarkers of cognitive deficit in SCZ.